The Impact of Technological Tools on English Curriculum Planning - Eby Delyani Sitompul; Maisyaroh Hasibuan; Sania Oktavia Nasution; Winda Aulia; Rahmi Fitriyani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to explore the impact of the use of technological tools on English curriculum planning in the modern era. Technology has become an important part of 21st century education, especially for generation Z who are very familiar with information and communication technology. This study identified significant benefits of technology, such as increased student engagement, self-directed learning, and the development of critical thinking skills. However, there are challenges that must be overcome, such as limited resources, inadequate teacher training, and potential distractions from non-educational content.This study used a qualitative approach, involving interviews with educators and surveys of students at the State Islamic University of North Sumatra. The results of the thematic analysis showed that technology integration can improve the quality of learning if these challenges are overcome through teacher training, cost-effective use of resources, and balanced technology use policies. Thus, technology can be a reliable and effective component in innovative and inclusive English curriculum planning.